(3fRgI GdfGXQjf aj JGQjN ef hdi eUQ ef GdNdaGA hGdSdGWjfs - (3eQYj Hf jhSa Hf CHj HcQ Hf CMeO GdcQej GdebOSj GdMfHdi,J (B1033 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdHGbi hcd ef YdjgG aGf s
(3Vef eLehY s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B203 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B218s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B496 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B276 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs